9-4x=2+3x

Simple and best practice solution for 9-4x=2+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-4x=2+3x equation:


Simplifying
9 + -4x = 2 + 3x

Solving
9 + -4x = 2 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
9 + -4x + -3x = 2 + 3x + -3x

Combine like terms: -4x + -3x = -7x
9 + -7x = 2 + 3x + -3x

Combine like terms: 3x + -3x = 0
9 + -7x = 2 + 0
9 + -7x = 2

Add '-9' to each side of the equation.
9 + -9 + -7x = 2 + -9

Combine like terms: 9 + -9 = 0
0 + -7x = 2 + -9
-7x = 2 + -9

Combine like terms: 2 + -9 = -7
-7x = -7

Divide each side by '-7'.
x = 1

Simplifying
x = 1

See similar equations:

| x+3x+7=25 | | 211.636*48.9/360*33.7= | | 13-x=-6 | | 642+189=p | | 10-z=-3 | | 5e^2+2e-7=0 | | 327-132=v | | 2*3.14*33.7= | | f=1702+1809 | | 5(2p+8)=2+6(p+5) | | 0.012y=0.7b-0.1071 | | x+45=430 | | -6x-13=-x-13 | | -(3x-7y+w)= | | 36/0.4 | | 11-4(2x-3)+3(x-10)-(3+x)-1=0 | | 25x+647=865x-688 | | s=1700-988 | | w(w+3)+204=(2w+6)(w-1) | | 8(5+4x)+50=154 | | y=(235-8x)/5 | | 15+40=h | | 9m^2+18m-13=0 | | (235-8x)/5 | | 140=(4x)(x+2) | | 24806*57.3/2= | | [x]=16 | | 7900/2 | | 30x+7=-24x+5 | | 22x+9-11= | | 22x-11+9= | | 37/4=y-4/3 |

Equations solver categories